Faktor-faktor yang Mempengaruhi Permintaan Tahu di Kecamatan Tampaksiring - MAHATMA, GEDE JAYENG; ANGGRENI, I GUSTI AYU AGUNG LIES; RANTAU, I KETUT (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.9, No.1, Januari 2020, 2020)
Factors that Influence the Demand for Tofu in Tampaksiring Sub-district This study aims to determine the factors that Influence the demand for tofu in the Tampaksiring District area. Location selection was done intentionally (porposive), sampling points were carried out in Pejeng Village and Tampaksiring Village. The population in this study is household consumers who buy and consume tofu and as decision makers in buying tofu. The samples taken were 60 people with accidental sampling technique. In this study using a multiple linear regression analysis model using statistical criteria namely F test, t test and R2.The results showed that the results of the F test were six variables, namely: price, price of tempe, price of eggs, number of family members, last education and family income together influencing the demand for tofu in Tampaksiring District. Partially the results of the t-test analysis show that at the 95% confidence level the variables that partially influence the demand for tofu in Tampaksiring District are the price, the price of tempeh, the price of eggs.The results of the study revealed that most people consume tofu based on the nutritional benefits contained in it. This is expected to be an opportunity for tofu entrepreneurs in Tampaksiring District to increase production and supply of tofu products in order to fulfill the demand for tofu in Tampaksiring Sub-district.